2013
DOI: 10.7763/ijssh.2013.v3.227
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Evaluation of Food and Beverage Companies in Thailand: An Application of Relational Two-Stage Data Envelopment Analysis

Abstract: Abstract-This study used a relational two-stage data envelopment analysis (DEA) to evaluate the efficiency of 23 food and beverage companies in Thailand in 2011. The whole production process of the companies can be divided into two sub-processes for analyzing the efficiency differences: production achievement and profit generation. The conclusion shows that the low efficiency score of the profit generation process leads to the low overall efficiency score of the companies.Index Terms-Food and beverage, data en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Bosnia and Herzegovina, Montenegro and Slovakia are found to be relatively inefficient in this dataset, whereas Croatia and Romania showed to be somewhere in the top middle. Rodmanee and Huang (2013) have used a relational two-stage DEA to evaluate the efficiency of 23 food and beverage companies. Mad Nasir et al (2011) also used the DEA approach to evaluate the market competitiveness of small and medium enterprises in the food industry.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Bosnia and Herzegovina, Montenegro and Slovakia are found to be relatively inefficient in this dataset, whereas Croatia and Romania showed to be somewhere in the top middle. Rodmanee and Huang (2013) have used a relational two-stage DEA to evaluate the efficiency of 23 food and beverage companies. Mad Nasir et al (2011) also used the DEA approach to evaluate the market competitiveness of small and medium enterprises in the food industry.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The first stage of the data analysis involves calculation of the scale efficiency and the technical efficiency in the version of Variable Return to Scale (VRS). Taking into account the studies of (Chen et al, 2015) and (Rodmanee and Huang, 2013) The results indicate that technical efficiency of sugar and confectionery producers were high and relatively stable during the analysed period (Fig. 2).…”
Section: Resultsmentioning
confidence: 91%
“…174-179 dairy products. In turn, Rodmanee and Huang testing efficiency of the food industry enterprises in Thailand with the two-stage DEA analysis found that enterprises with low operating profitability show low efficiency as well (Rodmanee and Huang, 2013). In Poland the research conducted with non-parametric DEA method on the meat processing enterprises operating in 2006-2011 indicates that during this period their average efficiency had an upward trend (Jarzębowski, 2014).…”
Section: Efficiency Of Food Enterprises -Literature Reviewmentioning
confidence: 99%
“…The findings of a US dairy product industry survey showed that productivity growth was negative, and both scale and technical changes had a negative impact [23]. In 2011, the efficiency of 23 food and beverage companies in Thailand was evaluated by Rodmanee and Huang [24] by adopting a relational two-stage DEA model. It was shown that a low overall efficiency score of companies is caused by a low efficiency score in the profit generation process.…”
Section: Literature Reviewmentioning
confidence: 99%